Experiences of probation officers working with children in conflict with the law at the Johannesburg Metro Region - Sibisi, Muntuwenkosi W (My University, 2015)
Crime is one of the world’s serious problems with numerous violent crimes being committed by children and young people. Similar trends have been noted in South Africa (Masuku, 2004). The primary aim of the research project was to explore the experiences of probation officers working with children in conflict with the law in the Johannesburg Metro Region. The research approach applied was qualitative in nature. The research used narrative research design. A non-probability sample of ten probation officers was selected purposefully from the Department of Social Development (DSD), Johannesburg Metro Region. Semi-structured interview schedule was used to collect data. Data triangulation was used to ensure trustworthiness of the study and two Magistrates of Children’s Court and two Prosecutors were also interviewed. The interviews were transcribed verbatim and thematic analysis was used to analyse the data. The main findings that emerged from the study were that, probation officers did not get specialized training on the Child Justice Act (CJA) subsequently leading to poor social service delivery to children in conflict with the law that they intervene with.